Effect of tourist vessels on the behaviour of the pantropical spotted dolphin, Stenella attenuata, in Drake Bay and Caño Island, Costa Rica - Montero-Cordero, Andrea; Lobo, Jorge (J. Cetacean Res. Manage., 2023)
Despite the exponential increase in whalewatching activities in Costa Rica, little is known about its biological impact on resident coastal populations of dolphins in the country. Globally, this activity has brought economic benefits to the communities where it is practiced and in some cases, has played an important role in conservation of these mammals. However, when intensively practiced, this activity may significantly affect the animals, since its success depends on following cetaceans for extended periods of time. This study was conducted during the 2004–2005 and 2005–2006 dry seasons, to examine the biological factors associated with this activity in two areas where it is intensively practiced: Drake Bay and Caño Island. Three strip transects were followed within a high (vessel) traffic area. The pantropical spotted dolphin was studied through instant sampling, every two minutes. Sighting density of dolphins accompanied by tourist boats was greater within 3km of the island compared to the average density in the whole study area. Dolphins reacted negatively to those boats that did not follow at least one of the rules of boat handling in the current existing national regulation for whalewatching guidelines. Furthermore, a logistic regression analysis showed that feeding and resting are less likely to occur in the presence of tourist boats. These two behaviours are extremely important and mishandled boats could cause the spotted dolphin to leave this area if these flaws continue. Due to the lack of economic resources and staff from state institutions in Costa Rica, the reinforcement of the Whalewatching Executive Decree 32495 (2005) may be more efficient with ‘bottom up’ control, where community representatives control their own resources in conjunction with government oversight.